2021
DOI: 10.1111/and.14245
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of oltipraz in testicular ischaemia/reperfusion injury: An experimental study

Abstract: Testicular torsion is an emergency urological disease, and the treatment is immediate surgery. Despite emergency surgery, testicular damage may occur due to reperfusion. Therefore, a medical treatment to prevent this damage may be a rational idea. We aimed to evaluate the protective effect of oltipraz in testicular ischaemia/reperfusion damage. Twenty‐eight Wistar–Albino rats were randomly divided into four groups. In ischaemia/reperfusion group, testicular torsion was executed, and orchiectomy was done 4 hr a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Testicular planimetry revealed that I/R significantly reduced the diameter and area of the seminiferous tubules (shrunken seminiferous tubules), the diameter of the seminiferous lumen, and epithelial height [ 6 , 7 ]. This is accompanied by distortion of testicular histoarchitecture evidenced by an increase in Cosentino's score, accumulation of inflammatory cells, intratubular oedema, and sloughing of the testicular germ cells [ 6 , 7 , 15 , 64 ].…”
Section: Consequences Of Testicular I/r Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular planimetry revealed that I/R significantly reduced the diameter and area of the seminiferous tubules (shrunken seminiferous tubules), the diameter of the seminiferous lumen, and epithelial height [ 6 , 7 ]. This is accompanied by distortion of testicular histoarchitecture evidenced by an increase in Cosentino's score, accumulation of inflammatory cells, intratubular oedema, and sloughing of the testicular germ cells [ 6 , 7 , 15 , 64 ].…”
Section: Consequences Of Testicular I/r Injurymentioning
confidence: 99%
“…In another experimental study, it was shown that oltipraz treatment has an advantageous effect to testicular I/R injury. Oltipraz exerts cytoprotective, antioxidant and anti-apoptotic activities [ 64 ]. Uguralp and his colleagues [ 116 ] reported that resveratrol diminished apoptosis in the ipsilateral testes but did not reduce apoptosis in the contralateral testes.…”
Section: Anti-diabeticsmentioning
confidence: 99%